Rene toner, falske nyheter: Skillingsviser i det tidligmoderne Skandinavia - Brandtzæg, Siv Gøril (K&K - Kultur og Klasse, 2020)
This article discusses skilling ballads as a news medium in the early modern period, and it suggests that in Scandinavia the news ballad was the most important journalistic genre for a broad public. Through a reading of ballads conveying news of fantastical creatures, the article considers how skilling ballads negotiated the borders between the true and the false, and how some of our contemporary mechanisms for revealing fake news can be detected in the early modern news ballads.